2022
DOI: 10.1002/smll.202105409
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in ZIF‐Derived Atomic Metal–N–C Electrocatalysts for Oxygen Reduction Reaction: Synthetic Strategies, Active Centers, and Stabilities

Abstract: oxidation reaction on the anode, while the oxygen undergoes a reduction reaction on the cathode. However, the sluggish kinetics and instability of oxygen reduction reaction (ORR) electrocatalysts, especially in the practical acidic and oxidation environments, have severely hindered their further developments. Therefore, engineering ORR electrocatalysts with high activity and good stability is desired to promote energy transformation efficiency. By far, the most popular ORR electrocatalysts are the costly plati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 142 publications
(323 reference statements)
0
37
0
Order By: Relevance
“…Specifically, cobalt-based N-doped carbon (Co–N–C) has emerged as a promising catalyst for oxygen electrocatalysis, attributed to its appropriate intermediate adsorption–desorption free energy of reaction dynamics. 9 Metal–organic frameworks (MOFs) assembled from metal nodes and organic ligands are good candidates for M–C x formation. 10 Generally, zeolitic imidazolate frameworks (ZIFs), composed of transition metal cations (Zn, Co, Fe, and Ni) and imidazole linkers, are used for M–N–C formation.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, cobalt-based N-doped carbon (Co–N–C) has emerged as a promising catalyst for oxygen electrocatalysis, attributed to its appropriate intermediate adsorption–desorption free energy of reaction dynamics. 9 Metal–organic frameworks (MOFs) assembled from metal nodes and organic ligands are good candidates for M–C x formation. 10 Generally, zeolitic imidazolate frameworks (ZIFs), composed of transition metal cations (Zn, Co, Fe, and Ni) and imidazole linkers, are used for M–N–C formation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the catalytic activity of transition metal-derived catalysts is mainly attributed to these M-N-C sites. 15,16 At present, it is generally believed that the active conguration of M-N-C SACs is M-N 4 , [17][18][19][20] among which the Fe-N 4 conguration shows superior ORR activity. [21][22][23] Xie et al 24 prepared Fe SACs containing FeN 4 single-atom sites with a half-wave potential (E 1/2 ) of 0.94 V (vs. RHE) in an alkaline electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…[9,[11][12][13] As a typical kind of porous materials, metal-organic frameworks (MOFs) represent an excellent precursor for pyrolysis synthesis of 3D porous FeÀ NÀ C catalysts. [14][15][16][17] In the meanwhile, metal-organic aerogels (MOAs) emerged as a novel porous material, which features unique micropores and mesopores resulted from its nano-scale MOF particles and interconnected network structure, respectively. [18][19][20] Owing to its ultra-high porosity and specific surface area, it has been widely used in adsorption, thermal batteries, catalysis, and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…In this regards, various 3D porous Fe−N−C catalysts have been explored for efficient ORR [9,11–13] . As a typical kind of porous materials, metal‐organic frameworks (MOFs) represent an excellent precursor for pyrolysis synthesis of 3D porous Fe−N−C catalysts [14–17] . In the meanwhile, metal‐organic aerogels (MOAs) emerged as a novel porous material, which features unique micropores and mesopores resulted from its nano‐scale MOF particles and interconnected network structure, respectively [18–20] .…”
Section: Introductionmentioning
confidence: 99%